Vertical Market Integration Analysis of Rice in Indonesia - Ginting, Nelva; Sinaga, Reflianta; Gea, Sary Yani (Formosa Journal of Applied Sciences, 2024)
Rice is a staple food in Indonesia, but challenges in the country's rice markets and marketing systems persist, leading to significant losses for both producers and consumers due to volatile price fluctuations. The prices of various food products are rising sharply due to growing demand driven by population growth, which is not adequately supported by supply. This study aims to examine the vertical market integration of rice in Indonesia using the Vector Error Correction Model (VECM) as the analytical method. The findings reveal that the markets for harvested dry grain at the producer level and rice at the consumer level are integrated in the long term, indicating that changes in producer-level harvested dry grain prices are influenced by consumer-level rice prices. However, this integration is not observed in the short term.